(untitled) (Revista Cientifica Ingenio Magno, 2023)
This paper presents a study related to the design of straws based on natural carrot cellulose, in which everything related to the design and development of straws is presented, taking into account the properties of materials, regulations, identification of users, typological analysis, requirements table, identification of the stages of the product extraction process to develop the design concept, creative process, development of technical drawings and sketches to transform and obtain the final product in straws for commercial use and B2B markets. All this based on the identification of different articles, works and researches, likewise, the production process of the biodegradable straw was carried out at laboratory scale; in this stage different tests were carried out for the creation of the prototype, with the results of these tests it was possible to successfully achieve the production of the biodegradable straw based on carrot cellulose.